INCREASING THE EFFICIENCY OF INVESTMENT IN THE DEVELOPMENT OF EXPORT DIVERSIFICATION IN THE REGION (Conference Zone, 2022)
This article discusses some issues such as increasing the efficiency of investment in the development of export diversification in the region , its components, the formation of diversification and the main factors of exports.